Emerging Developments on Pathogenicity, Molecular Virulence, Epidemiology and Clinical Symptoms of Current Middle East Respiratory Syndrome Coronavirus (MERS-CoV) - Subbaram, Kannan; Kannan, Hemalatha; Gatasheh, Mansour Khalil (HAYATI Journal of Biosciences, 2017)
Middle East respiratory syndrome coronavirus (MERS-CoV) is a recently reported virus that is associated with severe, life threatening and rapidly spreading primarily respiratory illness called the Middle East respiratory syndrome. MERS-CoV possesses a unique positive-sense single-stranded RNA and can undergo rapid mutation in the viral genome. This results in antigenic switching and genetic variation, finally leading to the emergence of novel and new MERS-CoV subtypes which are uncontrollable by vaccines. Researchers are also finding difficulties to sort out therapeutic intervention strategies for MERS-CoV. This virus can spread from human to human, but transmission from dromedary camels to humans plays a crucial epidemiological significance. Dromedary camel acts as “gene mixing vessels” for MERS-CoV and these virus particles undergo rapid change in them. Viral receptors called dipeptidyl peptidase-4 are important receptors for attachment and spread of MERS-CoV in humans. The current method of laboratory confirmation is through real-time polymerase chain reaction on bronchoalveolar lavage, sputum and tracheal aspirates. Unfortunately, till today there are no definite anti-viral drugs available for MERS-CoV.